Religious Engagement and Successful Aging among Korean Older Adults - You, Sukkyung (Religions, 2023)
The rate of aging is growing faster than ever. The global society must prepare adequate measures to support this imminent change. Following this social trend, research has been conducted on the quality of life of the aging population in a different fields, including gerontology. Since the idea of successful aging was conceptualised, research on the quality of life of older adults has been actively conducted. The current study aims to contribute to the aging research field by adding a factor (religious engagement) to Rowe and Kahn’s model. We utilized the longitudinal design to examine the longstanding effect of demographic, physical, social, psychological, and religious factors on life satisfaction among older Korean adults (N = 4013). Hierarchical regression analyses were employed to understand how these factors influence older adults’ life satisfaction in a nationally representative sample. Study findings indicated (a) after controlling for demographic background, all subdimensions of physical, social, psychological, and religious factors exerted a significant effect on later life satisfaction; (b) the final model showed that highly educated, regular exercise, frequent meeting with friends and family, less depressed, feeling less lonely, and higher religious engagement ultimately affected the subsequent life satisfaction of Korean older adults; (c) among different variables, psychological health and religious engagement were found to be crucial factors. The findings confirm the explanatory power of successful aging theory while providing empirical evidence that religious engagement may be an additional factor contributing to enhancing the life satisfaction of older adults.